Strategy of BMT Bima Magelang in Improving Public Welfare through Cash Waqf - Wicaksono, Muhamad Budi; Hartomi, Hartomi; Siddiq, Muhammad Rizky (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
Cash waqf is one of the methods used to help people with various activities and overcome challenges such as poverty reduction. The goal of this study was to determine excellent and proper cash waqf administration in line with Sharia and the standards of good waqf governance to increase social welfare, particularly in Baitul Maal Wa Tamwil Bima Magelang. This study employs qualitative research, with data gathered through structured interviews, passive participant observation, and recording. After that, the data was examined using qualitative descriptive analysis. The qualitative descriptive research approach describes the features of phenomena in the field and explains the study object. The findings of this study show that Baitul Maal Wa Tamwil Bima Magelang uses waqf management with the mudharabah system, with mudharabah financing allocated to goat farmers and Micro, small, and Medium Enterprises (MSMEs), and that in the management of cash waqf, BMT Bima Magelang implements good waqf governance, which improves social welfare through social programs. Profits from finance are then utilized to fund businesses and make loans. The revenues from the mudharabah are then utilized for financing (scholarships) for BMT members, financing for child circumcision, and rehabilitation of locals' houses that are unsuited for habitation. These several factors indicate that BMT Bima Magelang's cash waqf management is in conformity with cash standardization, good waqf governance, and sharia management. Implications of the findings that Islamic finance practices can be effective instruments in achieving sustainable social and economic development goals.